Breakers of glass ceilings: the professional careers of women in Finland and the graduates of three girls’ upper secondary schools (1890s–1910s) - Nieminen Marjo (Routledge, Taylor & Francis Group, 2022)
This article focuses on the occupational emancipation of women in Finland and examines the professional careers of women who graduated with a matriculation examination from three upper secondary girls’
schools during the period of the 1890s to the 1910s. One of the schools was for Finnish-speaking girls, and two of the schools were for Swedishspeaking girls. This article asks what kinds of educational paths and professional careers these upper secondary girls’ school graduates had during their lives after graduation. Attention is paid to both the typical professional careers and to those careers that could be characterised as exceptional and atypical. The source material consists of student registers that offered an opportunity to create a prosopography (i.e. set biography). In this article, the prosopography and individual biographies of women with exceptional careers shed light on the horizon of possibilities for Finnish women at the end of the nineteenth century and in the early twentieth century, specifically, their horizon of possibilities to gain education and degrees, as well as posts in the labour market.